Leading by Example, Ideas or Coercion? The Carbon Border Adjustment Mechanism as a Case of Hybrid EU Climate Leadership - Eva Pander Maat (European Papers, 2022)
(Series Information) European Papers - A Journal on Law and Integration, 2022 7(1), 55-67 | European Forum Insight of 29 April 2022 | (Table of Contents) I. The CBAM and EU leadership theory. - I.1. Introduction. - I.2. The CBAM: assertively combating carbon leakage. - I.3. EU climate unilateralism. - I.4. EU climate leadership: types. - I.5. EU climate leadership: objectives. - II. The CBAM as a case of exemplary/cognitive leadership. - III. The CBAM as a case of structural leadership. - IV. Pushing or pioneering? The CBAM in objectives. - V. Conclusion. | (Abstract) The Carbon Border Adjustment Mechanism (CBAM) is the most recent and assertive component of EU external climate policy. Whilst the CBAM has the potential to accelerate global climate governance, by demonstrating that Parties to the Paris Agreement can combat carbon leakage by means of border measures, it could simultaneously foster animosity and stall progress. Accordingly, the CBAM could either solidify or jeopardize the EU's long-recognized leadership position in global climate governance. This Insight therefore takes an in-depth look at the CBAM as a case of climate leadership. It assesses how the EU seeks to establish itself as a leader by merging methods from the exemplary, cognitive, and structural leadership types, whilst acting as a simultaneously economically and environmentally driven actor with high internal and external climate ambitions. This hybridity attests to the complexity of the CBAM, but also to the composite nature of EU climate leadership via unilateral measures. More specifically, the Insight brings attention to the close interrelation between exemplary and cognitive leadership in novel policy solutions, as well as the complementary role of structural leadership when there is no predetermined hierarchy between international norms. This role raises the question how sustainable EU climate unilateralism will be as the EU's economic clout, and hence its additional leverage, will decrease over time.